(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Автор статті робить спробу визначити особливості формування лідерських якостей майбутніх соціальних педагогів, а також роль цих якостей у майбутній професійній діяльності. Ключові слова: лідерство, лідерські якості, соціальний педагог. Author of the article makes an attempt to determine the features of the formation of leadership quality of future social workers, as well as the role of these qualities in future work professionally. Key words: leadership, leadership skills, social pedagogue.